(untitled) (Fiep Bulletin - online, 2016)
School violence is not a recent problem, and gradually turned into a serious social problem, especially if practiced repetitively called bullying. The objective of this work is to verify the profile and identify the behavioral pattern of students who practice bullying. The survey was conducted through a questionnaire, and participants are characterized by 165 students, with 97 male and 68 female students from across the state and municipal public schools in the municipality of Novo Cabrais - RS, aged 10 to 17 years. The attackers are characterized as being of the same class as the victim, in addition, the attacks usually come from a child or many children. It was concluded that this study found that the aggressors are mostly students from the same class as the victim, most beaten says tell parents about these abuses, most students say help colleagues as you can, and one of the options mentioned was "help beat", and with this mistaken attitude eventually raise this aggression index.